2016
DOI: 10.3390/polym8100339
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Polyurethane/Polylactide Sponges Doped with Nano-Hydroxyapatite (nHAp) Combined with Human Adipose-Derived Mesenchymal Stromal Stem Cells for Regenerative Medicine Applications

Abstract: Cartilage and bone tissue injuries are common targets in regenerative medicine. The degeneration of cartilage tissue results in tissue loss with a limited ability to regenerate. However, the application of mesenchymal stem cells in the course of such condition makes it possible to manage this disorder by improving the structure of the remaining tissue and even stimulating its regeneration. Nevertheless, in the case of significant tissue loss, standard local injection of cell suspensions is insufficient, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Our previous studies showed that (TPU + PLA) sponges with the 80:20 ratio induced osteogenic differentiation potential in ASCs (Marycz, Marędziak, Grzesiak, Lis, & Śmieszek, ). Here, we additionally incorporated 1 and 5% IONPs to analyze their effect on ASCs under normal and MF conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that (TPU + PLA) sponges with the 80:20 ratio induced osteogenic differentiation potential in ASCs (Marycz, Marędziak, Grzesiak, Lis, & Śmieszek, ). Here, we additionally incorporated 1 and 5% IONPs to analyze their effect on ASCs under normal and MF conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The porous matrices were prepared as previously described by our group (Marycz, Marędziak, Grzesiak, Lis, & Śmieszek, ). Polymers, as well as composite scaffolds, were produced by means of the solvent casting particulate leaching method.…”
Section: Methodsmentioning
confidence: 99%
“…The dehydrated tissues were left to air‐dry overnight. Then, the samples were coated with gold using ScanCoat6 (Edwards) and observed using a SE1 detector at a 10 kV filament tension (SEM, Zeiss Evo LS 15) (Marycz, Marędziak, Grzesiak, & Śmieszek, ). The study was performed in the Electron Microscopy Laboratory of the Wroclaw University (Wroclaw, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…In essence, we argue that ALP was not produced in the PLLA/AWf cultures because phosphate was already available in the media, but for PLLA/AWp and PLLA cultures it wasn't as prominent. Previous studies show that the ingestion of HA particles smaller than 50 µm could accelerate the osteogenic differentiation of human MSCs derived from adipose tissue [54].…”
Section: Cell Differentiation and Biomineralisationmentioning
confidence: 97%